2013
DOI: 10.1680/geolett.12.00042
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic shear response of fibre-reinforced cemented paste backfill

Abstract: In order to investigate techniques to improve tailings backfill stability in stopes, the cyclic shear response of fibre-reinforced cemented mine tailings was studied. Cyclic simple shear tests were conducted on fibre-reinforced and non-reinforced cemented mine tailings. The tailings, produced from gold mining, are classified as sandy silt with traces of clay. Portland cement (5%) and polypropylene fibres (zero and 0?5%) were added to the material. Under monotonic shear conditions, the addition of fibres confer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…So, in this study, 6 mm PP fibers were selected. For 20% cement content, the fiber contents (mixing amounts of the fiber relative to the dry weight of slurry) were 0%, 0.25%, 0.5%, 0.75%, and 1%, respectively, according to [14][15][16][17][18].…”
Section: Testing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, in this study, 6 mm PP fibers were selected. For 20% cement content, the fiber contents (mixing amounts of the fiber relative to the dry weight of slurry) were 0%, 0.25%, 0.5%, 0.75%, and 1%, respectively, according to [14][15][16][17][18].…”
Section: Testing Materialsmentioning
confidence: 99%
“…Various studies have been conducted to investigate the influences of fiber on the property of cemented soil through unconfined compression test or splitting strength testing [9][10][11]. Several scholars also performed triaxial test [12], direct shear test [13], bending test [14], isotropic compression test [15], and cyclic shear test [16] on fiber-admixed cemented soil. e studies showed that adding fiber into cemented sandy soil or clay with constant low cement content (less than 10%) could enhance its compressive strength, residual strength, and ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Simple shear tests have been used for many engineering and geology purposes, such as the study of mechanical behavior of sands (De Alba et al, 1976, Mao & Fahey, 2003, clays (Chu & Vucetic, 1992, Boulanger et al, 1993 and mine tailings (Wijewickreme et al, 2005, Wijewickreme et al, 2010, Festugato et al, 2013, Festugato et al, 2015, and the modeling of folding and fracture patterns (Price & Torok, 1989). The equipment development started with an apparatus by Kjellman (1951) to overcome some of the shortcomings of the traditional direct shear test, which suffers from non-uniform stress distribution throughout the specimen.…”
Section: Previous Workmentioning
confidence: 99%
“…This practice has been widely used, as described by Lin and Wong (1999), Andromalos et al (2001) and Hussin and Garbin (2012). The research group at Federal University of Rio Grande do Sul, Brazil (e.g., Thomé et al, 2005;Consoli et al, 2008Consoli et al, , 2009aConsoli et al, ,b,c, 2010Consoli et al, , 2011Consoli et al, , 2012Consoli et al, , 2013aConsoli et al, ,b, 2014aFestugato et al, 2013;Faro et al, 2015) has been studying key parameters dictating strength and stiffness of lime/cement treated soils.…”
Section: Introductionmentioning
confidence: 99%